Treatment outcomes in a safety observational study of dihydroartemisinin/piperaquine (Eurartesim®) in the treatment of uncomplicated malaria at public health facilities in four African countries. (December 2016) - Adjei, Alexander; Narh-Bana, Solomon; Amu, Alberta; Kukula, Vida; Nagai, Richard; Owusu-Agyei, Seth; Oduro, Abraham; Macete, Eusebio; Abdulla, Salim; Halidou, Tinto; Sie, Ali; Osei, Isaac; et al.
Abstract Background Dihydroartemisinin-piperaquine (DHA-PQ) is one of five WHO recommended artemisinin combination therapy (ACT) for the treatment of uncomplicated malaria. However, little was known on its post-registration safety and effectiveness in sub-Saharan Africa. DHA-PQ provides a long post-treatment prophylactic effect against re-infection; however, new infections have been reported within a few weeks of treatment, especially in children. This paper reports the clinical outcomes following administration of DHQ-PQ in real-life conditions in public health facilities in Burkina Faso, Ghana, Mozambique, and Tanzania for the treatment of confirmed uncomplicated malaria. Methods An observational, non-comparative, longitudinal study was conducted on 10, 591 patients with confirmed uncomplicated malaria visiting public health facilities within seven health and demographic surveillance system sites in four African countries (Ghana, Tanzania, Burkina Faso, Mozambique) between September 2013 and April 2014. Patients were treated with DHA-PQ based on body weight and followed up for 28 days to assess the clinical outcome. A nested cohort of 1002 was intensely followed up. Clinical outcome was assessed using the proportion of patients who reported signs and symptoms of malaria after completing 3 days of treatment. Results A total of 11, 097 patients were screened with 11, 017 enrolled, 94 were lost to follow-up, 332 withdrew and 10, 591 (96.1 %) patients aged 6 months–85 years met protocol requirements for analysis. Females were 52.8 and 48.5 % were <5 years of age. Malaria was diagnosed by microscopy and rapid diagnostic test in 69.8 % and 29.9 %, respectively. At day 28, the unadjusted risk of recurrent symptomatic parasitaemia was 0.5 % (51/10, 591). Most of the recurrent symptomatic malaria patients (76 %) were children <5 years. The mean haemoglobin level decreased from 10.6 g/dl on day 1 to 10.2 g/dl on day 7. There was no significant renal impairment in the nested cohort during the first 7 days of follow-up with minimal non-clinically significant changes noted in the liver enzymes. Conclusion DHA-PQ was effective and well tolerated in the treatment of uncomplicated malaria and provides an excellent alternative first-line ACT in sub-Saharan Africa.